Immunotherapy in advanced kidney cancer: an alternative meta-analytic method using reconstructed survival data in case of proportional hazard assumption violation - Nocera, Luigi; Fallara, Giuseppe; Raggi, Daniele; Belladelli, Federico; Robesti, Daniele; Montorsi, Francesco; Karakiewicz, Pierre I.; Malavaud, Bernard; Ploussard, Guillaume; Necchi, Andrea; Martini, Alberto (Frontiers in Oncology, 2022)
Background: With the advent of immuno-oncology compounds in randomized trials, we observe more and more survival curves crossing. From a statistical standpoint this corresponds to violation of the proportional hazard assumption. When this occurs, the hazard ratio from the Cox regression is not reliable as an estimate. Herein, we aimed to identify the most appropriate IO-based therapy for metastatic renal cell carcinoma applying an alternative method to overcome the issue of hazard assumption violation for meta-analyses. Methods: Pubmed, EMBASE, Web of Science and Scopus databases were searched. Only phase III randomized clinical trials on IO-IO (nivo-ipi) or IO-TKI combinations were included. An algorithm to obtain survival data from published Kaplan-Meier curves was used to reconstruct data on overall survival (OS), progression-free survival (PFS) and duration of response (DoR). Differences in restricted mean survival time (RMST) were used for comparisons. Results: individual survival data from 4,206 patients from five trials were reconciled. Patients who received nivo-ipi or IO-TKI had better OS, PFS and DoR relative to sunitinib (all p<0.001). Patients who received IO-TKI had similar OS and PFS relative to nivo-ipi, with a 36-month RMST of -0.55 (95% CI: -1.71-0.60; p=0.3) and -1.5 (95% CI: -2.9-0.0; p=0.051) months, respectively. Regarding DoR, patients who received nivo-ipi had longer duration of response relative to IO-TKI, with a 24-month RMST of 1.5 (95% CI: 0.2-2.8; p=0.02) months. Conclusion: Despite overall similar OS and PFS for patients receiving nivo-ipi and IO-TKI combinations, DoR was more favorable in patients who received nivo-ipi compared to IO-TKI. A meta-analysis based on differences in RMST is a useful alternative whenever the proportional hazard assumption is violated.